THE EXPERIENCE OF DEVELOPING SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN ECONOMICLY DEVELOPED COUNTRIES - Kulmatov, Alimjon; Elov , Dilshod (International Journal of Psychosocial Rehabilitation, 2020)
The article considers the development of small businesses and private entrepreneurship in economically developed countries, including innovative and high-tech enterprises as a strategic alternative to the formation of new markets. In this regard, an analysis of foreign countries on state support for foreign economic activity of small business and private entrepreneurship was carried out.